Choice and conscience: Lessons from South Africa for a global debate - Nabaneh, Satang (Pretoria University Law Press (PULP), 2023)
Choice and Conscience offers a fresh and insightful perspective on the highly debated issue of conscientious objection in abortion care. Satang Nabaneh's socio-legal approach, which draws on both traditional legal scholarship and African feminist intellectual traditions, provides a nuanced understanding of how legal norms construct and maintain power relations. By focusing on the experiences of nurses in South Africa, Nabaneh explores the complexities of conscience, discretionary power, and socio-cultural and political factors that influence nurses' decisions about whether or not to conscientiously object. In the wake of the recent rollback of abortion rights in the United States and the trend towards liberalisation within the African region, Nabaneh provides an important African perspective on how the international human rights framework should strike a contextual balance between freedom of conscience and ensuring access to abortion. Choice and Conscience will interest lawyers, activists, policymakers, scholars, and students exploring the dynamic intersections of law, healthcare, and gender politics. Choice and Conscience ... stands as a significant and valuable addition to the ongoing global scholarship on this critical issue. It underscores the vital concept that intersectionality should occupy a central place in our examination of how various local contexts give rise to layered forms of privilege and disadvantage. Dr Tlaleng Mofokeng, UN Special Rapporteur on the right to health ... Nabaneh's study of "law in action" zeros in on South African nurses--gatekeepers who often object to the practice for reasons of "conscience." Her interviews of these nurses and her analysis complicate our understanding of challenges to abortion access, providing lessons applicable not only to South Africa and other African countries, but everywhere where there is a gap between formal law and its application. Mindy Jane Roseman, JD, PhD, Yale Law School Written from an African feminist perspective, this book offers fresh insights into our understanding of the intersection between politics, mobilisation of discretionary power and the exercise of conscientious objection to abortion by mid-level providers. Charles Ngwena, Professor of Law, Centre for Human Rights, University of Pretoria This book offers powerful insights about how informal and background norms in health systems function constrain or enable reproductive justice. Focusing on conscientious objection to abortion by nurses (including midwives) in South Africa, Nabaneh sketches the importance of a feminist analysis that is situated in Africans' lived realities. Alicia Ely Yamin, Harvard University